A Comparative Survey of Serum Androgenic Hormones Levels between Male Patients with Dermatophytosis and Normal Subjects - Sarasgani, Mohammad Reza; Zomorodian, Kamiar; Hashemi, Seyed Jamal (Japanese Journal of Infectious Diseases, 2004)
Fungal growth can be influenced by human physiological mediators such as androgenic hormones. The aim of this study was to investigate a possible relationship between androgenic hormones and susceptibility to dermatophytosis. To this purpose we measured the levels of testosterone, androstendione, and dehydroepiandrosterone sulfate (DHEA-S) in 60 male patients with dermatophytosis due to Epidermophyton floccosum and Trichophyton rubrum by enzyme link immunoassay. Serum testosterone concentration was found to be significantly lower in patients with E. floccosum than in healthy subjects. No significant differences in androstendione and DHEA-S levels were noted between the patients and the healthy individuals. The results showed that testosterone concentration can be considered a predisposing factor for tinea cruris infection.